2008
DOI: 10.1111/j.1471-4159.2008.05556.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the neuronal response to ischaemia by somatostatin analogues in wild‐type and knock‐out mouse retinas

Abstract: Somatostatin acts at five G protein‐coupled receptors, sst1‐sst5. In mouse ischaemic retinas, the over‐expression of sst2 (as in sst1 knock‐out mice) results in the reduction of cell death and glutamate release. In this study, we reported that, in wild‐type retinas, somatostatin, the multireceptor ligand pasireotide and the sst2 agonist octreotide decreased ischaemia‐induced cell death and that octreotide also decreased glutamate release. In contrast, cell death was increased by blocking sst2 with cyanamide. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 71 publications
8
51
1
Order By: Relevance
“…These observations have been replicated in an ex vivo model of the ischemic mouse retina, where the neuroprotective effects of SRIF have been shown to be mediated by the sst2 receptor. Indeed, these studies showed that an increased expression of functional sst2 receptors [40] or the use of SRIF or SRIF receptor agonists, such as the multireceptor ligand pasireotide and the sst2 receptor agonist octreotide [41], are effective in reducing the number of apoptotic neurons, the expression of apoptotic markers, such as caspase-3 mRNA, and the release of glutamate. In contrast, cell death is significantly increased after blocking sst2 receptors with the sst2 receptor antagonist cyanamide [41].…”
Section: Neuropeptides As Anti-ischemic Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations have been replicated in an ex vivo model of the ischemic mouse retina, where the neuroprotective effects of SRIF have been shown to be mediated by the sst2 receptor. Indeed, these studies showed that an increased expression of functional sst2 receptors [40] or the use of SRIF or SRIF receptor agonists, such as the multireceptor ligand pasireotide and the sst2 receptor agonist octreotide [41], are effective in reducing the number of apoptotic neurons, the expression of apoptotic markers, such as caspase-3 mRNA, and the release of glutamate. In contrast, cell death is significantly increased after blocking sst2 receptors with the sst2 receptor antagonist cyanamide [41].…”
Section: Neuropeptides As Anti-ischemic Agentsmentioning
confidence: 99%
“…Indeed, these studies showed that an increased expression of functional sst2 receptors [40] or the use of SRIF or SRIF receptor agonists, such as the multireceptor ligand pasireotide and the sst2 receptor agonist octreotide [41], are effective in reducing the number of apoptotic neurons, the expression of apoptotic markers, such as caspase-3 mRNA, and the release of glutamate. In contrast, cell death is significantly increased after blocking sst2 receptors with the sst2 receptor antagonist cyanamide [41]. In addition, intravitreal administration of SRIF or sst2 receptor agonists, have been reported to protect the retina from AMPA-induced neurotoxicity in vivo [42].…”
Section: Neuropeptides As Anti-ischemic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…When indicated, GC cells were treated in the absence or in the presence of 100 nM SRIF (30 min) before the assay. Using published protocols (Cervia et al , 2008, total RNA was extracted with the RNeasy Mini Kit with DNAse digestion (Qiagen, Hilden, Germany), according to the manufacturer's recommended procedure. After solubilization in RNase-free water, total RNA was quantified by Bio-Rad SmartSpec 3000 spectrophotometer (Hercules, CA, USA).…”
Section: Rt-pcr Experimentsmentioning
confidence: 99%
“…This drug proved to be effective in delaying or to some extent reverting symptoms of DR (Grant et al, 2000). Acting on sst2 receptors, it may possibly control inflammatory processes (Pinter et al, 2006), endothelial symptoms (Cervia et al, 2012), and also to some extent neural symptoms (Cervia et al, 2008;Vasilaki and Thermos, 2009;Vasilaki et al, 2002). Additional peptide and nonpeptide analogs should be involved in future experiments.…”
Section: P0990mentioning
confidence: 99%